2022
DOI: 10.3390/vaccines10040552
|View full text |Cite
|
Sign up to set email alerts
|

The Beneficial Effect of the COVID-19 Vaccine Booster Dose among Healthcare Workers in an Infectious Diseases Center

Abstract: Introduction: Healthcare workers in Poland received a booster dose of the BNT162b2 mRNA vaccine (Pfizer-BioNTech, Manufacturer: Pfizer, Inc., and BioNTech; Moguncja, Germany) at the beginning of October 2021. Here, we report on the preliminary results of an ongoing clinical study into the antibody response to SARS-CoV-2 of healthcare workers previously exposed to the virus, with or without evidence of past infection, in the Hospital for Infectious Diseases in Warsaw before and after the vaccine booster dose. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…The results of our analysis were aimed to complement those published earlier by Skrzat-Klapaczy ńska and colleagues [1] on elucidating the effect of BNT162b2 booster immunization on anti-SARS-CoV-2 antibodies. For this purpose, we measured both total and IgG anti-SARS-CoV-2 antibodies, showing that both classes of antibodies considerably increased (by 31 and 22-fold, respectively) 1 month after receiving the BNT162b2 vaccine booster.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…The results of our analysis were aimed to complement those published earlier by Skrzat-Klapaczy ńska and colleagues [1] on elucidating the effect of BNT162b2 booster immunization on anti-SARS-CoV-2 antibodies. For this purpose, we measured both total and IgG anti-SARS-CoV-2 antibodies, showing that both classes of antibodies considerably increased (by 31 and 22-fold, respectively) 1 month after receiving the BNT162b2 vaccine booster.…”
Section: Discussionmentioning
confidence: 62%
“…In a recent article published in this journal, Skrzat-Klapaczy ńska and colleagues [1] showed that a booster dose of the mRNA-based BNT162b2 vaccine was effective at increasing the serum values of SARS-CoV-2 IgG antibodies measured with the MAGLUMI SARS-CoV-2 S-RBD IgG assay over the maximum measurable level according to the method used by the authors (i.e., >433 BAU/mL). To provide further insights on this important aspect in terms of limiting SARS-CoV-2 infection and lowering the risk of developing serious complications from coronavirus disease 2019 (COVID-19), we monitored both total and IgG anti-SARS-CoV-2 antibodies response after BNT162b2 vaccine booster immunization in a cohort of ostensibly healthy healthcare workers, with a specific focus on emphasizing the potential correlation between the post-booster variation of these two antibodies classes.…”
Section: Introductionmentioning
confidence: 99%
“…In general, there is agreement that individuals who have received two doses of COVID-19 vaccines should receive additional doses periodically [18]. Such additional doses have been shown to be beneficial and safe [19][20][21][22]. Additional doses are also strongly recommended for adults with underlying health conditions living in long-term care and for those living in high-risk environments [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Antibody titers declined more rapidly in subjects with mild/asymptomatic SARS-CoV-2 infection [ 15 , 16 , 17 , 18 , 19 ]. A decreased trend of humoral immunity is also evident in vaccinated individuals after the second vaccine dose [ 7 , 20 ]; however, scarce data exist analyzing humoral responses after the administration of a third dose of the vaccine [ 21 , 22 ], and even fewer data focus on the ability of this vaccine to generate mucosal humoral immune responses.…”
Section: Introductionmentioning
confidence: 99%